Endophytic fungi associated with Monarda citriodora, an aromatic and medicinal plant and their biocontrol potential - Meenu Katoch; Shipra Pull (Taylor & Francis Group, 2017)
Context: The Food and Agriculture Organization has estimated that every year considerable losses of the food crops occur due to plant diseases. Although fungicides are extensively used for management of plant diseases, they are expensive and hazardous to the environment and human health. Alternatively, biological control is the safe way to overcome the effects of plant diseases and to sustain agriculture. Since Monarda citriodora Cerv. ex Lag. (Lamiaceae/Labiatae) is known for its antifungal properties, it was chosen for the study. Objective: The isolation of endophytic fungi from M. citriodora and assessing their biocontrol potential. Material and methods: The isolated endophytes were characterized using ITS-5.8 S rDNA sequencing. Their biocontrol potential was assessed using different antagonistic assays against major plant pathogens. Results: Twenty-eight endophytes representing 11 genera were isolated, of which, around 82% endophytes showed biocontrol potential against plant pathogens. MC-2 L (Fusarium oxysporum), MC-14 F (F. oxysporum), MC-22 F (F. oxysporum) and MC-25 F (F. redolens) displayed significant antagonistic activity against all the tested pathogens. Interestingly, MC-10 L (Muscodor yucatanensis) completely inhibited the growth of Sclerotinia sp., Colletotrichum capsici, Aspergillus flavus and A. fumigatus in dual culture assay, whereas MC-8 L (A. oryzae) and MC-9 L (Penicillium commune) completely inhibited the growth of the Sclerotinia sp. in fumigation assay. Conclusions: Endophytes MC-2 L, MC-14 F, MC-22 F and MC-25 F could effectively be used to control broad range of phytopathogens, while MC-10 L, MC-8 L and MC-9 L could be used to control specific pathogens. Secondly, endophytes showing varying degrees of antagonism in different assays represented the chemo-diversity not only as promising biocontrol agents but also as a resource of defensive and bioactive metabolites.